2010
DOI: 10.1038/nature09586
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hydroxylation of 5-methylcytosine in myeloid cancers with mutant TET2

Abstract: TET2 is a close relative of TET1, an enzyme that converts 5-methylcytosine (5-mC) to 5-hydroxymethylcytosine (5-hmC) in DNA1,2. The gene encoding TET2 resides at chromosome 4q24, in a region showing recurrent microdeletions and copy-neutral loss of heterozygosity (CN-LOH) in patients with diverse myeloid malignancies3. Somatic TET2 mutations are frequently observed in myelodysplastic syndromes (MDS), myeloproliferative neoplasms (MPN), MDS/MPN overlap syndromes including chronic myelomonocytic leukemia (CMML),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,101
4
23

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,162 publications
(1,171 citation statements)
references
References 26 publications
43
1,101
4
23
Order By: Relevance
“…5-Hydroxymethylation of cytosine bases (5-hmC) is a newly identified epigenetic marker; this nontraditional DNA modification involves methylation of cytosine bases (5-mC) in CpG dinucleotide sequences 2,3 and their oxidation by the ten-eleven translocation (TET) family of proteins. While 5-hmC is a potentially useful indicator of disease states such as cancer [4][5][6][7][8] , the mechanisms controlling its abundance in tumours and its impact on gene expression and cancer cell fate are unclear.…”
mentioning
confidence: 99%
“…5-Hydroxymethylation of cytosine bases (5-hmC) is a newly identified epigenetic marker; this nontraditional DNA modification involves methylation of cytosine bases (5-mC) in CpG dinucleotide sequences 2,3 and their oxidation by the ten-eleven translocation (TET) family of proteins. While 5-hmC is a potentially useful indicator of disease states such as cancer [4][5][6][7][8] , the mechanisms controlling its abundance in tumours and its impact on gene expression and cancer cell fate are unclear.…”
mentioning
confidence: 99%
“…In support of this idea, studies have predominantly demonstrated hypermethylation signatures in both TET2-and IDH-mutant acute myeloid leukemias, 28 as well as in IDHmutant gliomas 29 and enchondromas, 32 although other authors have reported conflicting results. 41 However, although inhibition of TET function appears to be associated with DNA hypermethylation, it remains unclear how these epigenetic changes regulate gene expression, as studies have, as of yet, failed to demonstrate direct links between changes in the promoter methylation status of specific genes and alterations in the expression levels of those genes. This may reflect the fact that although epigenetic changes can alter the accessibility of loci to transcriptional machinery, additional factors, including the availability of transcription factors, coactivators, and corepressors, also have a role in dictating changes in gene expression.…”
Section: -Hydroxymethylcytosine In Sdh-deficient Gistmentioning
confidence: 99%
“…TET2 mutations occur across several of the gene's 12 exons. 4 TET proteins catalyze conversion of 5-methylcytosine to 5-hydroxymethylcytosine, 28,29 and, accordingly, TET2 mutations are thought to contribute to epigenetic dysregulation of transcription. TET2 mutational frequencies are estimated at 16% in PV, 5% in ET, 17% in PMF, and 17% in blast-phase MPN.…”
Section: Overview Of Mutations Associated With Bcr-abl1-negative Mpnsmentioning
confidence: 99%
“…19,[37][38][39] TET2, ASXL1, and EZH2 mutations might contribute to epigenetic dysregulation of transcription. 28,29,31 …”
Section: Jak2 and Mpl Mutation Tests In Mpns 463mentioning
confidence: 99%